Kajian radiologi alam sekitar di Iskandar Malaysia, Johor, Malaysia - Abu Hanifah, Noor Zati Hani (2015)
This study has been conducted to estimate the risk from ionizing radiation and to obtain baseline data for environmental radiological assessment for Iskandar Malaysia, Johor, Malaysia. The terrestrial gamma dose rate data were collected. Samples of soil, water, flora and fauna were collected and analysed to obtain the natural radionuclide concentrations of 226Ra, 232Th and 40K. Samples of soil, flora and fauna were analysed using gamma spectrometer, hyper pure germanium (HPGe). Water samples were analysed using an induced coupled plasma mass spectrometer (ICP-MS) and atomic absorption spectrometer (AAS). Alpha and beta radioactivity level was obtained using alpha-beta spectrometer. The correction factor value, Cf for this study is 0.795. The terrestrial gamma dose rate for each district in Iskandar Malaysia ranged from 74 nGy h-1 to 168 nGy h-1. The average activity concentrations for gross alpha-beta, 226Ra 232Th and 40K in the soil samples were 796 Bq kg-1, 864 Bq kg-1 , 67 Bq kg-1, 94 Bq kg-1 and 177 Bq kg-1 respectively. The average of activity concentrations for gross alpha-beta, 226Ra 232Th and 40K in the flora and fauna sample were 4.5 mBq kg-1, 87 mBq kg-1, 2 mBq kg-1 and 60 mBq kg-1 respectively. The average activity concentrations for gross alpha-beta, 226Ra 232Th and 40K in surface river water were 0.02 Bq l-1, 0.14 Bq l-1, 23 mBq l-1, 2 mBq l-1 and 51 Bq l-1 respectively. The average total annual effective dose from ingestion of water, flora and fauna is 0.4 mSv per year. The cancer risk probability for Iskandar Malaysia population were estimated to be 5.9 x 10-5 per year from annual effective gamma dose in air and dose from ingestion of alpha, beta and gamma emitters’ radionuclide. The population weighted dose rate in Iskandar Malaysia region is 127 nGy h-1. As a conclusion, population in Iskandar Malaysia receive terrestrial gamma dose rate more than twice the world average but this is still within the normal range and not expected to cause any health concern